Techniques for creating high quality compost in an effort to reduce fertilizer cost - Tirtopawiro, Laurenzo (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Mr. Bryan Smith, Agriculture Specialist, Jamaica Social Investment Fund (JSIF) - Jamaica, Mr. Mario Lewis, Co-Founder, International Network of Innovative Partners for Sustainable Intelligent Systems (Inipsis Ltd.) - Trinidad & Tobago